Borboletas frugívoras (Lepidoptera : Nymphalidae) da Floresta Nacional de Passo Fundo, Rio Grande do Sul, Brasil - Ribeiro, Caroline da Silva (2022)
The Atlantic Forest is home to one of the greatest biological diversities in the world, however, this precious biodiversity has been devastated in recent years. With this in mind, it is essential that we make efforts, especially in conservation units, so that we have knowledge of the occurrence and behavior of these species and, with that, preserve them. Butterflies are charismatic and maintain a close relationship with plant species. The Atlantic Forest is home to one of the greatest biological diversities in the world, however, this precious biodiversity has been devastated in recent years. With that in mind, it is imperative that we make efforts, especially in U.C.s, so that we have knowledge of the occurrence and behavior of these species and, with that, we can preserve them. Butterflies are charismatic and maintain a strict relationship with plant species. In the present work we seek to identify the butterflies that occur in the National Forest of Passo Fundo (Flona PF), aiming to solve the knowledge gap about the lepidopterofauna of the northern region of Rio Grande do Sul. For this purpose, we used eight areas of Flona PF to carry out active sampling of nectarivorous butterflies and, in only five areas, we also have Van Someren Rydon (VSR) model traps for passive sampling and attraction of frugivorous butterflies. Active sampling took place in five monthly sampling events, from November 2021 to March 2022, and passive sampling took place over nine days monthly between January and December 2021, resulting in 70h of active sampling and 77,250h of passive sampling. A total of 169 species were recorded, with 123 nectarivorous species accounting for 363 individuals and 46 frugivorous species accounting for 5,840 individuals. Nymphalidae was the richest family, covering about 50% of the species. We found common species, as well as rarer species, for example, Arcas ducalis (Westwood, 1852) found only in preserved environments. The number of species found in Flona PF shows the importance of the U.C., making it essential for regional biodiversity. Necessary information about insect-plant interactions was also discovered in the present study, promoting knowledge about the species that occur in the Atlantic Forest, also opening spaces for more questions and future work with these species. Still, another result of the sampling was the creation of a guide of frugivorous butterflies occurring in the Passo Fundo National Forest that will help in the dissemination of the knowledge generated here.